A. B. Jackson and the 'black art' paradigm. Issue 3 (1st September 2013) - McGuire, Kathryn Waggener
This brief biography introduces the life of American painter Alexander Brooks 'A. B.' Jackson (1925–1981) and seeks to better establish his place in the annals of American Art and Education history. A student of renowned colour field painter Josef Albers at Yale, and the first black professor at Old Dominion University in Virginia, Jackson represents a connection between the teaching methods of Germany's Bauhaus design school and the politics and aesthetics of segregation in America during the 1960s and 1970s. Art by African American artists of Jackson's generation is often examined either in terms of a radicalized political stance, or in the context of abstract expressionism – often linked to the self-described (or presumed) rhythm and attitudes of African American identity. Jackson's work and professional identity did not adhere to the trends spurred by the nation's heated racial tensions, and therefore defies current educational and aesthetic categorization. A deeper understanding of Jackson's experience, methods as an artist, and greater body of work are sought through interviews, archival research, and an examination of why his presence amongst the greater perception of 'black art' is largely omitted from scholarly resources.